2023
DOI: 10.48550/arxiv.2302.09906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing production networks from firm growth dynamics

Abstract: We study the correlation structure of firm growth rates. We show that most firms are correlated because of their exposure to a common factor but that firms linked through the supply chain exhibit a stronger correlation on average than firms that are not. Removing this common factor significantly reduces the average correlation between two firms with no relationship in the supply chain while maintaining a significant correlation between two firms that are linked. We then demonstrate how this observation can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…They spread negative or positive shocks from one firm to its customers and suppliers, generating correlations between firms' fundamentals, such as market valuation and sales [58][59][60]. Starting from this observation and leveraging the graph learning literature, Mungo and Moran [42] introduce a method to reconstruct the production network from the time series of firm sales, s i (t). First, the authors show empirically that the correlation between the log-growth rates of firms connected in the production network surpasses the average correlation yielded by randomly sampled firm pairs, and this excess correlation decreases as firms get further apart in the supply chain.…”
Section: Leveraging the Correlation Matrix Using Graph Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…They spread negative or positive shocks from one firm to its customers and suppliers, generating correlations between firms' fundamentals, such as market valuation and sales [58][59][60]. Starting from this observation and leveraging the graph learning literature, Mungo and Moran [42] introduce a method to reconstruct the production network from the time series of firm sales, s i (t). First, the authors show empirically that the correlation between the log-growth rates of firms connected in the production network surpasses the average correlation yielded by randomly sampled firm pairs, and this excess correlation decreases as firms get further apart in the supply chain.…”
Section: Leveraging the Correlation Matrix Using Graph Learningmentioning
confidence: 99%
“…A related question for further research will be to establish the potential of 'dynamical' data. Mungo and Moran [42] showed that while there is information about the network in the sales growth rates correlation matrix, predicting the network remains difficult, as the distribution of pairwise correlation for connected and unconnected pairs overlaps greatly, even though their average is statistically significantly different. Nevertheless, there are interesting developments in this area for networks generally, with only one application to supply networks.…”
Section: What Have We Learned?mentioning
confidence: 99%